Risk of dementia or cognitive impairment in COPD patients: A meta-analysis of cohort studies - Jun Wang; Jun Wang; Xuanlin Li; Xuanlin Li; Siyuan Lei; Siyuan Lei; Dong Zhang; Dong Zhang; Shujuan Zhang; Shujuan Zhang; Hailong Zhang; Hailong Zhang; et al. (Frontiers in Aging Neuroscience, 2022)
PurposeA meta-analysis of cohort studies was performed to evaluate the association between COPD and the risk of dementia or cognitive impairment.MethodsCohort studies that evaluated the association between COPD and the risk of dementia or cognitive impairment were identified by a systematic search of PubMed, Embase, Web of Science, and Cochrane Library databases. The search time frame was from database establishment to April 12, 2022, with two reviewers independently screening the literature and extracting data. The Newcastle-Ottawa Quality Assessment Scale (NOS) was used to conduct the quality evaluation. Then, a meta-analysis was performed using Stata 15.1 software.ResultsSix cohort studies including 428,030 participants were included. The overall quality of the included studies was high, with an average NOS score of over 7. Meta-analysis showed that compared to those without COPD at baseline, patients with COPD were associated with a significant increased risk of dementia (RR = 1.24, 95% CI = 1.03 ~ 1.50, I2 = 96.6%, z = 2.25, p = 0.024) and cognitive impairment (RR = 1.30, 95% CI = 1.13 ~ 1.49, I2 = 50.1%, z = 3.72, p < 0.001). Subgroup analysis suggested no significant difference in the risk of dementia among COPD patients of different genders. Nevertheless, in terms of age, the risk of dementia varied among COPD patients of different ages, which was most distinguished in patients younger than 65 years.ConclusionCOPD patients have a higher risk of developing dementia or cognitive impairment compared to those without COPD, and this risk is not affected by gender but seems to be associated with age.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022325832.